Occurrence and distribution of PAHs in stranded dolphin tissues from the Northwestern Mediterranean. (June 2023) - Dron, Julien; Wafo, Emmanuel; Boissery, Pierre; Dhermain, Frank; Bouchoucha, Marc; Chamaret, Philippe; Lafitte, Daniel
Abstract: There are few cetacean tissue-specific polycyclic aromatic hydrocarbon (PAH) concentration studies in the Mediterranean, despite this region is among the most subjected to chemical contamination. PAH analyses were conducted in different tissues of striped dolphins ( Stenella coeruleoalba, N = 64) and bottlenose dolphins ( Tursiops truncatus, N = 9) stranded along the French Mediterranean coastline from 2010 to 2016. Comparable levels were measured in S. coeruleoalba and T. trucantus (1020 and 981 ng g −1 lipid weight in blubber, 228 and 238 ng g −1 dry weight in muscle, respectively). The results suggested a slight effect of maternal transfer. The greatest levels were recorded by urban and industrial centers, and decreasing temporal trends were observed in males muscle and kidney, but not in other tissues. As a conclusion, the elevated levels measured could represent a serious threat to dolphins populations in this region, particularly by urban and industrial centers. Graphical abstract: Unlabelled Image Highlights: PAH were elevated in Stenella coeruleoalba and Tursiops truncatus . Lower levels in S. coeruleoalba females suggest little maternal transfer. Naphthalene, fluorene, 5- and 6-rings PAHs dominated in all tissues. Highest levels were localized by urban and industrial areas. Constant time trends in blubber and liver, possibly decreasing in muscle and kidney.